284 Hypertrophic Variant of Cutaneous Graft Vs Host Disease Clinically Mimicking a Drug Reaction: A Case Report. (11th January 2018) - Mann, Steven; Kuhar, Matthew
Abstract: Graft vs host disease (GVHD) is a multisystemic disorder that is a frequent complication of allogeneic stem cell transplantation (ASCT). Skin manifestations are the most common clinical presentation and several histomorphologic variants exist. We present a rare case of cutaneous GVHD with hypertrophic morphology. A 2-year-old girl with a history of recurrent AML presented with a diffuse, blanchable, erythematous rash that began 2 months prior on her lower legs and then spread to her trunk and face. The rash was initially tender but progressed to desquamating plaques admixed with hyperpigmented patches. This occurred in association with a clinical trial of cytarabine and daunorubicin as well as several antibiotic courses including vancomycin and cefepime. She was on tacrolimus and methylprednisolone for a previous episode of GVHD. Recently, methotrexate therapy was initiated with concurrent weaning of her immunosuppressive medications. At an outside institution, the current rash was clinically diagnosed as a drug reaction without performing a biopsy due to eosinophilia and systemic symptoms. The rash worsened despite topical triamcinolone. New purple-red large, indurated plaques and smaller pink papules erupted on all extremities and punch biopsies were taken from this and the older trunk rash. Skin biopsies showed apoptotic junctional keratinocytes in association with a sparse intraepidermal lymphocyte population, supportive of GVHD, with the additional finding of significant epidermal acanthosis in the specimen from the older portion of the rash. The patient's steroid dose was increased and the rash faded over the subsequent days. Unfortunately, the patient died one week later with evidence of sepsis. Hypertrophic GVHD is perhaps the least well-documented and least reported histomorphologic cutaneous variant. It is important to be aware of this variant in order to render an accurate diagnosis, especially since it may be mistaken for lupus or even squamous cell carcinoma in florid examples.